The Influence of Load Modes on the Resource Reliability of Engine Parts of Agricultural Machinery - Pylyov, V. O.; Linkov, O.; Samoilenko, D.; Kravchenko, S. O.; Pylyov, V. V.; Mordivintseva, I.; Lykov, S. (Kaunas University of Technology, 2020)
The most common power unit for agricultural machinery is a diesel engine. The requirements for them are constantly being tightened. Modern diesel engines must comply with a wide range of requirements for ecology, efficiency and reliability. The article considers the impact of operational cycles of the agricultural machinery engines that operate in the Baltic countries, Poland, Ukraine and Kazakhstan on the design reliability of the piston engine. In view of this fact in the article the features of unsteady heat-stressed state of the piston and its impact on the time of trouble-free operation are considered.
Keywords: diesel engine; field furrow length; operation cyclicity; operation model; piston; combustion chamber edge; heat-stressed state; damage buildup; physical reliability